2020
DOI: 10.1039/c9qm00748b
|View full text |Cite
|
Sign up to set email alerts
|

In situ formed methyl-co-(bis-R) silsesquioxane based polymer networks with solvent controlled pore size distributions and high surface areas

Abstract: Specific pore size distributions of synthesized methylsilsesquioxane-based network materials stem from a combination of the solvation of monomers and growing oligomers, as well as miscibility of water in tested solvents; enabling specific analyte uptake materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…Changing to larger cage corners for each of the cross-linkers tended to show decreases in overall surface area, except when both corners and cross-linkers contained π-bonds. These studies will enable further understanding of post-synthesis modifiable silsesquioxane networks.Materials 2020, 13, 1849 2 of 13 of reaction solvent and water content in modifying the overall pore size distributions of a single cross-linker system [29]. Though many reports speculate that the pore sizes obtained in sol-gel reactions are directly related to the bridging groups used, especially for rigid spacers [2,26,[30][31][32], we found that multiple pore size distributions (0.5 to 100 nm) could be obtained by simply changing the reaction solvent for the same bridge.…”
mentioning
confidence: 72%
See 4 more Smart Citations
“…Changing to larger cage corners for each of the cross-linkers tended to show decreases in overall surface area, except when both corners and cross-linkers contained π-bonds. These studies will enable further understanding of post-synthesis modifiable silsesquioxane networks.Materials 2020, 13, 1849 2 of 13 of reaction solvent and water content in modifying the overall pore size distributions of a single cross-linker system [29]. Though many reports speculate that the pore sizes obtained in sol-gel reactions are directly related to the bridging groups used, especially for rigid spacers [2,26,[30][31][32], we found that multiple pore size distributions (0.5 to 100 nm) could be obtained by simply changing the reaction solvent for the same bridge.…”
mentioning
confidence: 72%
“…Sol-gel reaction efficiencies were measured by TGA, based on analysis of post-curing wt. % drops at~200 • C. We compared three cross-linkers against BTSE systems: [29] bis-triethoxysilylhexane (BTSH), bis-triethoxysilylethene (BTSEE), and bis-triethoxysilylacetylene (BTSA). We used a ratio of 1:0.36 of R-Si(OEt) 3 to cross-linker for our standard conditions, as they have been found to offer the highest surface areas and best overall reaction completion [29].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations